UNDERSTANDING INDONESIA LANGUAGE AND CULTURE AT LONGQI ELEMENTARY SCHOOL TAINAN – TAIWAN R.O.C. - Mustakim Mustakim; Tsai, Me-Tuan; Elihami Eihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2020)
The community service activities need to be carried out especially on Indonesian culture, so that Indonesia is not known only Bali but from Sabang to Merauke, community service activities run smoothly despite obstacles but it did not become a barrier for the implementation of activities, the community service benefits to the KSU students which at first they did not know about Indonesian culture, to some extent they have gained knowledge and understanding of Indonesian culture. The auspices of the Chinese Language Center Kun Shan University Tainan -Taiwan. The dedication activity carried out was to introduce Indonesian cultureto elementary school students namely Longqi Elementary School, Longqi District, Tainan Taiwan R.O.C.In this community service activity, it was carried out by STKIP Muhammadiyah Enrekang lecturers and Kun Shan University students. This dedication was done collaboratively so that there would be interaction between students and lecturers from Indonesia.In this service, we did not specify a specific problem, but rather how Indonesian culture is known by elementary school students and university students.